Modelling the impact of increase in sugar prices on dental caries in India. Issue 5 (26th August 2021) - Gupta, Arpit; Sharda, Shweta; Jyani, Gaurav; Prinja, Shankar; Goyal, Ashima; Gauba, Krishan
Abstract: Objectives: This study aims to assess the impact of raising the price of sugar and/or sugar‐sweetened beverages (SSBs) on caries incidence in the Indian population. Methods: A tooth‐level decision‐analytic model was developed to evaluate a change in caries increment after increasing the price of Sugar and SSBs. The transition of a tooth from a caries‐free state to the state of tooth loss in both scenarios was modelled with the help of a Markov model for a time horizon of 63 years, ranging from 2021 to 2083 for the 12‐year‐old population cohort of India. A conceptual framework was designed to implicate the possible effects of an increase in sugar prices on the reduction of caries incidence. Health effects were estimated in terms of the number of carious lesions and tooth‐loss in both the scenarios and modelled as a product of the dose‐response relationship between sugar intake and caries incidence. The model was thus used to establish the number of caries lesions prevented, and tooth‐loss avoided. Uncertainties in the parameters were assessed using probabilistic sensitivity analysis. The Monte Carlo method was used for simulating the results 999 times. Results: A 20% rise in the price of sugar is expected to result in the prevention of an average of 1.32 teeth in a lifetime of an individual and prevent 27.96 million tooth‐loss incidents among the population cohort of India that will eventually lead to a saving of INR (₹) 3116.32 billion (US$ 42.69 billion) on account of dental caries treatment. Similarly, increasing‐price of SSBs by 20% will lead to a 0.86% reduction in carious teeth incidence in an individual's lifetime. Conclusion: Increasing the cost of sugar and/or SSBs will reduce the daily intake of sugar, which will reduce caries incidence and subsequent progression, thereby preventing caries‐attributed tooth‐loss and saving treatment costs.